A new Drepanosticta species from Seram, Moluccas (Odonata: Platystictidae) - Tol, Jan Van; Bedjanič, Matjaž (Zootaxa, 2018)
Drepanosticta seramensis sp. nov. (holotype ♂: Indonesia, Moluccas, Seram Island, 36 km SW of Wahai, S 2.9768, E 129.2269; 2-xii-1996; deposited in RMNH, Leiden), is described as new to science. It is closely related to D. moluccana Lieftinck, 1938 from Buru and D. amboinensis van Tol, 2007 from Ambon.